Anticipating and Preparing for Emerging Skills and Jobs Key Issues, Concerns, and Prospects - Panth, Brajesh; Maclean, Rupert (Education in the Asia-Pacific Region: Issues, Concerns and Prospects,, 2020)
This open access book analyzes the main drivers that are influencing the dramatic evolution of work in Asia and the Pacific and identifies the implications for education and training in the region. It also assesses how education and training philosophies, curricula, and pedagogy can be reshaped to produce workers with the skills required to meet the emerging demands of the Fourth Industrial Revolution. The book's 40 articles cover a wide range of topics and reflect the diverse perspectives of the eminent policy makers, practitioners, and researchers who authored them. To maximize its potential impact, this Springer-Asian Development Bank co-publication has been made available as open access.